Enhancing fish waste quality through silage production: a review - Yuli Andriani; Rusky I Pratama; Muhamad Fatah Wiyatna; Hasna Nabila Shobihah (Depik, 2024)
The untapped potential of fish processing production waste as a source of fish feed ingredients makes it a promising resource due to its widespread availability. This study aims to evaluate the process of producing fish waste silage through probiotic fermentation to assess the resulting quality post-fermentation. Employing an exploratory descriptive method, this research draws from diverse literature sources, encompassing books, national journals, and international publications. The comparison of findings from prior research indicates that fermenting fish waste with microbes, particularly lactic acid bacteria, enhances its protein content, positively impacting fish growth performance. Introducing silage at a 10% dose achieves a tilapia survival rate of 83.33%, while a 25% silage addition yields a relative growth rate of 222.63% for catfish and a feed conversion ratio of 1.06 for tilapia.Keywords:FermentationFish wasteFish silageLactic acid bacteria